Enablers for Adoption of E-Learning Technology in Anti-Money Laundering Training in UAE Banks - Al Hammadi, Alya Hussain (2007)
A Master of Science Thesis in Engineering Systems Management Submitted by Alya Hussain Al Hammadi Entitled, "Enablers for Adoption of E-Learning Technology in Anti-Money Laundering Training in UAE Banks," May 2007. Available are both Soft and Hard Copies of Thesis.